STUDY ON THE PREVALENCE OF GALLSTONES IN PATIENTS UNDERGOING CHOLECYSTECTOMY IN BENAZIR BHUTTO SHAHEED HOSPITAL (DHQ) ABBOTTABAD - Jadoon, Sara; Nawaz, Muhammad; Javed, Sumaira; Imtiaz, Humaira; Jadoon, Omair; Taimoor, Alruba (Journal of Ayub Medical College Abbottabad, 2021)
Background: The incidence of gall bladder diseases is increasing day by day in developing as well as developed countries. Most common gall bladder diseases include gallstones (cholelithiasis) and cancer of gall bladder. Objective: To determine and compare the surgical incidence of gallstones on the basis of gender and age in patients undergoing elective cholecystectomy in Benazir Bhutto Shaheed Hospital (DHQ) Abbottabad. Methods: This was a descriptive study which was carried out for a period of one year from January 2017 to December 2017 in surgical unit of Benazir Bhutto Shaheed Hospital Abbottabad on patients who had cholecystectomy secondary to symptomatic gall stone disease diagnosed on the basis of history and ultrasonography. Gallstones were then analysed for bilirubin, cholesterol, calcium and phosphate. The data was analysed by using SPSS Version 16.00. Results: In our research study 88% of patients were females while 11.8% were males, the mean age being 35.81±8.12 year. The frequencies of different types of gall stones were: mixed type of stones 80.0% and cholesterol stones 20.0% Conclusion: Cholecystectomy secondary to gallstones is more common in women of forty to sixty age groups as compared to men of same age. Majority of gall stones are of mixed type. Keywords: Cholelithiasis/Gallstones; Elective cholecystectomy